Practicing social work in the digital era - Hoàng Thị Thu Thủy; Trương Thị Ly (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
In the digital age, a major challenge for social work is harnessing and leveraging technological advances for the benefit of clients and society. Despite the slow start, technology is beginning to infiltrate the work of social workers. Despite facing many difficulties in putting technology into practice, social workers are adapting and able to use technology in their practice. Social workers may be able to provide services to clients using online counseling, telephone counseling, video counseling, self-guided web-based interventions, or the use of social media. The application of technology has the potential to dramatically change, create practice innovations, and improve the effectiveness of social work practice over the next decade.